Narrative comprehension in 5-year-old Vietnamese-speaking children using the multilingual assessment instrument for narratives - Nguyen Thi Hoang Yen; Ben Phạm; Hang Pham; Van Pham; Phuong Nguyen; Phuong Bui (International Journal of Evaluation and Research in Education (IJERE), 2026)
This study addresses how elicitation modes and socio-demographic factors influence narrative macrostructure understanding in 5-year-old Vietnamese-speaking children. A convenience sampling of 311 typically developing children were assessed using the multilingual assessment instrument for narratives (MAIN). Narrative comprehension was evaluated through 10 standardized questions for both retelling (cat story) and storytelling (baby goats story) modes. Findings revealed a significant advantage for retelling (M=7.21, SD=2.31) over storytelling (M=5.73, SD=2.50; p<.001), highlighting the role of linguistic scaffolding. While children mastered identifying character goals, challenges remained in explaining internal states and making causal inferences. Narrative comprehension was independent of gender, location, and general communication skills, but significantly influenced by maternal education level (p<.05). Vietnamese narrative development follows universal patterns, yet deep comprehension is shaped by specific environmental inputs. This study establishes a normative baseline for narrative skills within the Vietnamese preschool curriculum and provides a validated tool for speech and language therapists to facilitate early identification and targeted interventions.